2022
DOI: 10.3389/fpsyg.2022.829567
|View full text |Cite
|
Sign up to set email alerts
|

Chief Executive Officer Tenacity and Employee Intrapreneurial Behavior: The Mediating Role of Corporate Social Responsibility

Zheng Huang

Abstract: Chief executive officer (CEO) tenacity plays an important role in corporate entrepreneurial activity. However, much less is known about its impact on employee intrapreneurship. Drawing from social information processing theory and upper echelons theory, this article examines the hitherto unexplored nexus between CEO tenacity and employee intrapreneurship, as well as the mediating role of corporate social responsibility (CSR). Quantitative data were collected through a survey administered to 294 employees worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…According to the upper echelons theory (Hambrick and Mason, 1984), top executives are the decision-makers behind CSR initiatives, and their values, experience and perceptions can determine the thinking processes and the strategic choices of enterprises, which ultimately affect CSR (Godos-Dı ´ez et al, 2020;Pan et al, 2020). In line with this view, scholars have found that the attributes of top executives such as tenacity (Huang, 2022), political ideologies (Chin et al, 2013) and academic background (Ma et al, 2020), significantly affect CSR. Previous studies have indicated that CSR is an important determinant in stimulating green innovation (Halkos and Skouloudis, 2018;Kraus et al, 2020;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the upper echelons theory (Hambrick and Mason, 1984), top executives are the decision-makers behind CSR initiatives, and their values, experience and perceptions can determine the thinking processes and the strategic choices of enterprises, which ultimately affect CSR (Godos-Dı ´ez et al, 2020;Pan et al, 2020). In line with this view, scholars have found that the attributes of top executives such as tenacity (Huang, 2022), political ideologies (Chin et al, 2013) and academic background (Ma et al, 2020), significantly affect CSR. Previous studies have indicated that CSR is an important determinant in stimulating green innovation (Halkos and Skouloudis, 2018;Kraus et al, 2020;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The upper echelons theory has been used in organizational management literature to explain how leaders impact the decision-making process and corporate behaviors (Hambrick and Mason, 1984). Thus, top executives play a crucial role in the strategic decision-making choices of companies (Huang, 2022). In addition, Huang (2022) further argues that corporate social responsibility (CSR) is based on strategic decision-making choices of top management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, when employees feel that the organization is belittling their contributions and well-being, they reduce their emotional commitment to the organization and their performance. Therefore, ensuring POS for telecommuting employees in order to stabilize their performance has become a major challenge for organizational management during the pandemic [2].…”
Section: Introductionmentioning
confidence: 99%